INVESTIGATION OF THE RELATIONSHIP OF ATTITUDES TOWARDS SPORTS AND INTERNET ADDICTION IN UNIVERSITY STUDENTS - Çakır, Fatmanur; Sıngın, Rabia Hürrem Özdurak (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
The aim of this study was to investigate the relationship between university students’ attitudes towards sports and their internet addiction. The participations of the present research were consisted of 314 students (female 153, male 161) from faculties of theology, communication, engineering, health sciences and sports sciences from 314 undergraduate students studying at Hitit University Faculty of Engineering and Theology, Gaziantep University Faculty of Health Sciences, Kastamonu University Faculty of Communication and Ankara University Faculty of Sport Sciences in 2018-2019 academic year. The mean age of the participants was as 21.47 (±1.97). Data of the study were collected with personal information form, “Undergraduate Students’ Attitudes Towards Sport Scale” and “Internet Addiction Test”. SPSS 22 program was used in the analysis of the obtained data. KolmogorovSmirnov test was applied to determine whether the data showed normal distribution and the level of significance was accepted as (p<0.05). In this research, a significant relationship between university students’ attitudes towards sports and internet addiction levels was tested as the main hypothesis of the research. As a result of the research; there was no significant relationship between participants’ attitudes towards sports and internet addiction levels (p>0.05). Also, it was found that the male students’ internet addiction level was higher than the female students. Besides, the addiction level increased as the age increased. The faculty of health sciences students’ internet addiction level was significantly different from the other faculty students and faculty of sport sciences students’ attitudes towards sports was also significantly higher (p<0.05). According to the results of the study, it was seen that internet addiction was quite common among students. However, it can be said sports can be used to protect university students from internet addiction.